Cordyceps sinensis relieves non-small cell lung cancer by inhibiting the MAPK pathway - Lu, Tianming; Zhou, Lirun; Chu, Zheng; Song, Yang; Wang, Qixin; Zhao, Minghong; Dai, Chuanhao; Chen, Lin; Cheng, Guangqing; Wang, Jigang; Guo, Qiuyan (Chinese medicine, 2024)
To determine the pharmacodynamic mechanism underlying Cordyceps sinensis relief in a murine model of non-small cell lung cancer (NSCLC). We created a murine model of NSCLC and studied the potential molecular mechanism by which C. sinensis relieved NSCLC using a combination of transcriptomics, proteomics, and experimental validation. C. sinensis markedly suppressed the fluorescence values in mice with NSCLC, improved the pathologic morphology of lung tissue, ameliorated inflammatory cytokines (tumor necrosis factor-alpha, interleukin-6, interleukin-10, and the oxidative stress indicators superoxide dismutase, malondialdehyde, and glutathione peroxidase). Transcriptomics results showed that the therapeutic effect of C. sinensis was primarily involved in the differentiation and activation of T cells. Based on the proteomic results, C. sinensis likely exerted a protective effect by recruiting immune cells and suppressing tumor cell proliferation via the MAPK pathway. Finally, the experimental validation results indicated that C. sinensis significantly decreased the VEGF and Ki67 expression, downregulated RhoA, Raf-1, and c-fos expression, which are related to cell migration and invasion, increased the serum concentration of hematopoietic factors (EPO and GM-CSF), and improved the percentage of immune cells (natural killer cells, dendritic cells, and CD4 and CD8 lymphocytes), which enhanced immune function. Based on our preclinical study, C. sinensis was shown to exert a protective effect on NSCLC, primarily by inhibiting the MAPK pathway.